Checkpoint Inhibitors Modulate Plasticity of Innate Lymphoid Cells in Peripheral Blood of Patients With Hepatocellular Carcinoma - Heinrich, Bernd; Ruf, Benjamin; Subramanyam, Varun; Myojin, Yuta; Lai, Chunwei W.; Craig, Amanda J.; Fu, Jianyang; Xie, Changqing; Kroemer, Alexander; Greten, Tim F.; Korangy, Firouzeh (Frontiers in Immunology, 2022)
Introduction The role of innate lymphoid cells (ILC) in cancer and specifically in the context of hepatocellular carcinoma (HCC) is not well understood. Immune checkpoint inhibitors (ICI) have been approved for treatment of patients with HCC. The effect of ICI on ILCs has not been explored. Methods We studied ILCs in PBMCs of 51 patients with HCC at baseline and after treatment with ICI. Flow cytometry was used to study ILC composition. Single-cell RNA-sequencing using a targeted panel of 405 immune-related genes was used to characterize the transcriptomic profiles as well as cellular trajectory of ILCs before and after ICI therapy. Intracellular cytokine staining was used to validate ILC function. Data from large patient cohorts were used to predict association with survival. Results Characterization of the ILC subgroups in PBMCs of HCC patients revealed a significant increase in ILC1 and a decrease in ILC3 frequencies. Single cell RNA-sequencing identified a subgroup of NK-like ILCs which expressed cytotoxicity markers as well as NKp80/KLRF1. This KLRF1high-NK-like population showed low abundance in patients with HCC and was enhanced after combined anti-CTLA-4 and anti-PD-1 immunotherapy. Trajectory analysis placed this population in between ILC1 and ILC3s. The transcriptomic signature of KLRF1high NK-like ILCs was associated with better progression-free survival in HCC cohorts. Conclusions We present a previously unknown effect of HCC tumors and ICIs on the composition and plasticity of ILCs in PBMCs. We identified a cytotoxic KLRF1high-NK-like subgroup which was associated with better survival, absent in untreated HCC patients, and enhanced upon ICI immunotherapy. Thus, ILCs from PBMC can be used to study changes in the innate immune system under immunotherapy.